Finance and the Good Society (an excerpt) - ShillerRobert J. (Journal of Economic Sociology, 2014)
Robert J. Shiller is the Professor of Economics at Yale University and the co-creator of the Standard& Poor’s Case–Shiller Home Price Indices. His book is devoted to financial capitalism, implying a system in which finance has taken the lead as the engine driving capitalism. The author is mostly interested in searching an answer to the question how we can make financial institutions work better for all of us. To achieve this purpose, Shiller develops a theory of financial capitalism in which finance is defined as the science of goal architecture. It is proposed that finance can contribute to success achievement and construction of the good society. The presented book by Shiller describes realities of the modern financial capitalism and proposes the critical reflections on it. The author also tries to relief the tension between human values and the issue of welfare concentration. The journal “Economic Sociology” publishes an excerpt of this book— “Introduction: Finance, Stewardship, and Our Goals”, in which the author problematizes the public hostility toward financial capitalism and seemingly profound contradiction between finance and the good society. The author demonstrates what kind of distinctive treats financial capitalism gets after the information age has come. Finally, Shiller proposes a working theory of financial capitalism.